Investigating perceptions of 'dose creep' amongst student radiographers: A grounded theory study. Issue 2 (May 2021) - Benfield, S.; Hewis, J.D.; Hayre, C.M.
Abstract: Introduction: The dose creep phenomenon is now a widely recognized concept in diagnostic radiography in light of recent technological advancements transnationally. However, this still remains underexplored amongst radiography students preparing to enter the radiography profession. In response, this study explores the perceptions of dose creep amongst undergraduate student radiographers. Methods: The methodological approach utilized in this research study was grounded theory. The qualitative approach aimed to uncover findings from a higher education institution in Australia. Six students were recruited and took part in semi-structured interviews. This enabled the exploration of previously uncovered data, leading to the construction of original theory within the clinical and academic environment. The data analysis employed was constant comparative analysis (CCA). Results: A number of insights emerged from the qualitative data set. For instance, the radiography students understanding of the term 'dose creep' and decision making leading to dose creep in the clinical environment is captured. This is further supported with assessment of image evaluation determining appropriate exposure factor selection and future impact upon graduation as diagnostic radiographers. The findings identify some important learning needs and actions for both clinical and academic settings which may help foster good use of X-ray exposures. Conclusion: This paper concludes by affirming some challenges surrounding optimal exposure selection and the known phenomenon, dose creep. Further, this study identifies the importance of learning and teaching in the clinical environment whereby learned behaviour leads to suboptimum practices. Implications for practice: This study advances the existing evidence base by providing a unique lens into the knowledge and understanding of dose creep amongst radiography students in both academic and clinical contexts. It is anticipated this paper will help practitioners and educators better understand potential instances of dose creep within the clinical environment.